Evolution of the Quality of water used in Palestinian haemodialysis centers - Aseel Salahat; Ayah Basim; Sarah Sofan (My University, 2016)
Dialysis fluid contamination problem due to the use of unpurified water is a common problem worldwide. Chemical and microbiological contaminants in dialysis fluid could cross the dialyzer membrane and cause harm to dialysis patients. In this study we evaluated the quality of water used in haemodialysis centers in the West Bank, Palestine. The results showed that the water quality in the majority of dialysis centers does not comply with the minimum requirement of haemodialysis water. Our study revealed an evidence of chemical and bacterial contamination in the dialysis centers in Palestine.